PENGARUH KOMUNIKASI YANG EFEKTIF DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT LANGKAT NUSANTARA KEPONG KANTOR KEBUN GOHOR LAMA - Azmi, Nurul; Syahrial, Hery (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2016)
This research aims to determine : 1)The effect of Effective Communication on Performance Employee  in  PT  Langkat  Nusantara  Kepong  Kantor  Kebun  Gohor  Lama.  2)  The  effect  of Motivation  on  Performance  Employee  in  PT  Langkat  Nusantara  Kepong  Kantor  Kebun  Gohor Lama. 3) The effect of Effective Communication and Motivation on Performance Employee in PT Langkat Nusantara Kepong Kantor Kebun Gohor Lama. The Types of this research is associative research.  Analysis  technique  of  this  research  is  multiple  regression  analysis.  Population  of  this research are the 56 employees at PT Langkat Nusantara Kepong Kantor Kebun Gohor Lama. The technique of sampling used boring sampling. This research data sourced from primary data and process data collection using questionnaires. The result of this research are : As partially effective communication variable has positive effect and significant on performance employee variable, on the  value  of  partial  test  is  (3.807  >  1.674).  Motivation  variable  has  positive  effect  and  not significant on performance employee variable, on the value of partial test is (1.082 < 1,674). And as  simultantly  effective  communication  and  motivation  have  positive  effect  and  significant  on performance employee, on the value of simultantly test is (13.735 > 3.17).Keyword : Effective Communication, Work Motivation, Performance Employe.